2015
DOI: 10.1007/s10854-015-3775-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of energy-storage properties of K0.5Na0.5NbO3 modified Na0.5Bi0.5TiO3–K0.5Bi0.5TiO3 lead-free ceramics

Abstract: A lead-free ceramics (1 -x)(0.84Na 0.5 Bi 0.5 TiO 3 -0.16K 0.5 Bi 0.5 TiO 3 )-xK 0.5 Na 0.5 NbO 3 (x = 0, 0.03, 0.06, 0.09, 0.12, 0.15) for energy-storage application have been fabricated by conventional solid state method. All compositions were crystallized into perovskite solid solution structure ascertained by XRD. SEM micrograph revealed that homogeneous grain could be obtained by addition of appropriate K 0.5 Na 0.5 NbO 3 (KNN). The depolarization temperature (T d ) decreased significantly from 140 to 70°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The largest W total , W rec ,and W loss were obtained at x = 0.06 and are 3.0, 1.5, and 1.5 J/cm 3 respectively. The values are superior to most KNN‐based ceramics that have been previously reported . As x increases, the change in the energy storage efficiency η is opposite of the change in W , as shown in Figure B.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The largest W total , W rec ,and W loss were obtained at x = 0.06 and are 3.0, 1.5, and 1.5 J/cm 3 respectively. The values are superior to most KNN‐based ceramics that have been previously reported . As x increases, the change in the energy storage efficiency η is opposite of the change in W , as shown in Figure B.…”
Section: Resultsmentioning
confidence: 72%
“…However, almost all the KNN‐based ferroelectric ceramics examined in previous studies do not satisfy the requirement of both high optical transmittance and high energy storage density. Tables and show the visible optical transparency and energy storage density of most KNN‐based ceramics studied during the 2014‐2017 time period . It was found that transparent ferroelectric ceramics with high energy storage densities have rarely been created in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The average grain size decreases systematically as NN content increases, ranging from ~8.3 μm for x = 0.02 to ~5.8 μm for x = 0.08. This effect is attributed to the lower diffusion rate for Nb 5+ ions and the consequent reduction in grain growth rates during high‐temperature sintering …”
Section: Resultsmentioning
confidence: 99%
“…However, its application in energy storage is limited owing to its large remanent polarization ( P r ) ∼ 38 μC cm −2 . 9 In recent decades, binary solid solutions formed by BNT and other perovskite materials have been explored, for instance, Bi 0.5 Na 0.5 TiO 3 –BaTiO 3 (BNTBT), 10 Bi 0.5 Na 0.5 TiO 3 –SrTiO 3 (BNTST), 11 Bi 0.5 Na 0.5 TiO 3 –Bi 0.5 K 0.5 TiO 3 (BNTBKT), 12 etc. Among them, (1 − x )Bi 0.5 Na 0.5 TiO 3 – x BaTiO 3 (BNTBT) ceramics exhibit favorable piezoelectric and ferroelectric performance with a 6% BaTiO 3 content, but its P r is still relatively large.…”
Section: Introductionmentioning
confidence: 99%